2019
DOI: 10.3390/genes10121012
|View full text |Cite
|
Sign up to set email alerts
|

Plant Hormones Differentially Control the Sub-Cellular Localization of Plasma Membrane Microdomains during the Early Stage of Soybean Nodulation

Abstract: Phytohormones regulate the mutualistic symbiotic interaction between legumes and rhizobia, nitrogen-fixing soil bacteria, notably by controlling the formation of the infection thread in the root hair (RH). At the cellular level, the formation of the infection thread is promoted by the translocation of plasma membrane microdomains at the tip of the RH. We hypothesize that phytohormones regulate the translocation of plasma membrane microdomains to regulate infection thread formation. Accordingly, we treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…This gives an idea of a possible SA contribution in the nodulation process, independent of plant immunity mechanisms. This is consistent with the recently described role of SA in the regulation of the subcellular localization of plasma membrane microdomains, which is essential during the early stage of nodulation in soybeans [265].…”
Section: Sa Couples Root Morphology and Plant-soil Biota Interactionssupporting
confidence: 93%
“…This gives an idea of a possible SA contribution in the nodulation process, independent of plant immunity mechanisms. This is consistent with the recently described role of SA in the regulation of the subcellular localization of plasma membrane microdomains, which is essential during the early stage of nodulation in soybeans [265].…”
Section: Sa Couples Root Morphology and Plant-soil Biota Interactionssupporting
confidence: 93%
“…These include enzymes such as the E3 ubiquitin ligase in L. japonicus [ 87 ], the putative E3 ubiquitin ligase with the Nodule specific RING finger domain (LjnsRING) in L. japonicus [ 163 ], the E3 ubiquitin ligase with ‘zinc finger’ type domain, Seven in absentia (MtSINA) in M. truncatula [ 164 ] and Cystathionine-β-synthase-like1 (MtCBS1) in M. truncatula [ 165 ]. Recently, using pea gibberellin-deficient and della -deficient mutants, it was shown that the phytohormone gibberellin suppresses the formation of infection threads [ 166 ], and its amount in infection threads is much lower than in bacteroids [ 167 ], on the contrary, phytohormones cytokinins and auxins play an important role in the development and propagation of infection threads, as well as in the release of bacteria from infection droplets [ 132 , 168 , 169 , 170 ]. A putative role of ethylene in infection thread maturation was also suggested [ 171 ].…”
Section: Propagation Of the Infection Threadmentioning
confidence: 99%
“…Plant hormones also play an important role in controlling the translocation of microdomains in specific regions of the plasma membrane. Treatment of transgenic soybean roots clearly revealed that GmFWL1 and GmFLOT2 are both translocated at the tip of the root hair cells in response to auxin and salicylic acid [71], hormones regulating nodulation and plant-microbe interactions [72][73][74][75][76]. Conversely, cytokinin inhibits this re-location [71] and the infection of root hair cell by rhizobia [77][78][79][80].…”
Section: Regulation Of the Subcellular Localization Of Fwl/cnr Proteinsmentioning
confidence: 99%
“…Treatment of transgenic soybean roots clearly revealed that GmFWL1 and GmFLOT2 are both translocated at the tip of the root hair cells in response to auxin and salicylic acid [71], hormones regulating nodulation and plant-microbe interactions [72][73][74][75][76]. Conversely, cytokinin inhibits this re-location [71] and the infection of root hair cell by rhizobia [77][78][79][80]. Consequently, it is tempting to speculate that plant hormones control plant-microbe interactions [81][82][83][84][85][86] by controlling the distribution of microdomains in the plasma membrane.…”
Section: Regulation Of the Subcellular Localization Of Fwl/cnr Proteinsmentioning
confidence: 99%